ANALISIS STRATEGI PEMANFAATAN LIMBAH TANAMAN PANGAN SEBAGAI PAKAN RUMINANSIA DI SULAWESI SELATAN - Jasmal A. Syamsu; Agustina Abdullah (Muhammadiyah University Press, 2009)
Vector Auto Regression (VAR) is an analysis or statistic method which can be used to predict time series variable and to analyst dynamic impact of disturbance factor in the variable system. In addition, VAR analysis is very useful to assess the interrelationship between economic variables. This research through the following test phases: unit root test, test of hypothesis, Granger causality test, and form a vector autoregresion model (VAR). The data used in this research is the GDP data and budget data of South Sulawesi in the period 1985-2004. The research aims to analyze the interrelationship between public expenditure and economic growth in South Sulawesi. The result showed statistically significant in economic growth (PDRB) influence public expenditure (APBD), however, not vice versa. Otherwise, for the need of APBD prediction, the used of lag 4 was the optimum model based on the causal relationship to PDRB.